(untitled) (Polis (Santiago), 2018)
The first part of this article offers a panoramic view of the New Science constituted during XXth century. The second part describes how the Person Centered Approach, of Carl Rogers, assumes the New Science, under the theoretical point of view, and takes it to a high practical level of excellence, first in therapy, then in education and, later, in all interpersonal and social relationship. The article ends indicating the original lines of the of phenomenological investigation tradition, characteristic of this approach since its birth during the 40’s of the XXth century.